Biosynthesis of Gold Nanostructures and Their Virucidal Activity Against Influenza a Virus - Segura-Segura, R; Segura-Segura, R; Arenas-Salinas, F; Cortez-San Martin, M; Contreras-Tobar, F; Liendo-Ibarra, F; Liendo-Ibarra, F (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Bacteria in natural environments often encounter high concentrations of metal ions, leading to the development of defense mechanisms such as chemical reduction. This process can result in the formation of nanostructures (NS) ranging from 1–100 nm, which have valuable properties for various applications, including as virucidal agents. Currently, metallic NS with virucidal activity are used in disinfectants and surface protection products. However, their production mainly relies on physical and chemical methods, which are often complex, toxic, and energy-intensive. A sustainable alternative is the biosynthesis of nanostructures. Our research focuses on the biosynthesis of gold nanostructures (AuNS) using environmental bacteria and their proteins, with the aim of exploring their potential as agents to destroy the influenza A virus. We screened bacteria under conditions with HAuCl4, identifying eight microorganisms capable of growing in high gold concentrations. Staphylococcus haemolyticus BNF01 showed the highest resistance and Au(III) reduction, growing up to 0.25 mM in HAuCl4. Bioinformatic analysis revealed five proteins with potential Au(III)-reductase activity, which were cloned and expressed in Escherichia coli. These proteins reduced gold to form AuNPs, which were purified, characterized for size, shape, and surface charge, and tested against influenza A, showing significant virucidal effects, likely due to interactions with viral proteins. © 2025 by the authors.